2023
DOI: 10.1111/ijpo.13065
|View full text |Cite
|
Sign up to set email alerts
|

Changes in insulin resistance, body mass index and degree of obesity among junior high school students: A comparison before and after the outbreak of the COVID‐19 pandemic

Abstract: SummaryThis study aimed to investigate how the COVID‐19 pandemic since 2020 has affected the homeostasis model assessment of insulin resistance (HOMA‐IR), body mass index (BMI) and degree of obesity among Japanese children. HOMA‐IR, BMI and degree of obesity were calculated for 378 children 14–15 years old (boys/girls, 208/170) who underwent checkups during 2015–2021. Changes in these parameters over time and correlations between parameters were assessed, and the proportions of participants with IR (HOMA‐IR ≥2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…16,17 In this study, we also found that the detection rate of depression in junior high school students was significantly higher than in high school students, and the detection rate and depression scores of students from rural areas were significantly higher than students from cities. The mental health status of rural children is not optimistic, and the reasons are as follows: (1) junior high school students are in a period of hormone fluctuation; 18 (2) Rural students' knowledge is relatively narrow, their parents' education level is low, their family happiness index is low, and they may not pay attention to the changes of students' emotions, which makes rural students more likely to bury many complex emotions, thus leading to depression; 19 (3) Rural economic development is low, and the ratio of mental health teachers is insufficient. 20 Our results show that middle school students, we need to understand their emotional state and pay more attention to them to detect their depression in time and solve it in time, especially for rural students and junior high school students.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In this study, we also found that the detection rate of depression in junior high school students was significantly higher than in high school students, and the detection rate and depression scores of students from rural areas were significantly higher than students from cities. The mental health status of rural children is not optimistic, and the reasons are as follows: (1) junior high school students are in a period of hormone fluctuation; 18 (2) Rural students' knowledge is relatively narrow, their parents' education level is low, their family happiness index is low, and they may not pay attention to the changes of students' emotions, which makes rural students more likely to bury many complex emotions, thus leading to depression; 19 (3) Rural economic development is low, and the ratio of mental health teachers is insufficient. 20 Our results show that middle school students, we need to understand their emotional state and pay more attention to them to detect their depression in time and solve it in time, especially for rural students and junior high school students.…”
Section: Discussionmentioning
confidence: 99%